EEG-based brain functional connectivity dynamics in manual and video-based car-following observation among young drivers - Peihao Li; Geqi Qi; Shuo Zhao; Ailing Huang; Wei Guan (Cognitive Neurodynamics, 2026)

Citrinin-controlled quinoa bioactivation and phenolic stabilization via mixed-Monascus fermentation and whey protein encapsulation - Lijia Liu; Ailing Deng; Xiaochun Su; Shubo Li; Yuan Guo (Food Bioscience, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Protein persulfidation in plants: a central regulator of multiple signaling pathways - Di Yang; Dengjing Huang; Xinfang Chen; Ailing Li; Huan Chen; Weibiao Liao (Plant Cell Reports, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Quantitative genetic architecture of growth traits across sequential rearing phases in tiger pufferfish (Takifugu rubripes) - Yangzhen Li; Clémence Fraslin; Ailing Wu; Haomin Lyu; Haien Zhang; Diego Robledo; Robert Mukiibi; Widong Li; Songlin Chen (Aquaculture, 2026)

Rapid evolution of life history of two water fleas in response to inter-specific competition - Jiasheng Yang; Jianan Li; Ailing Yan; Haoran Zhang; Qianqian Wei; Xiaodong Jiang (Journal of Oceanology and Limnology, 2026)

Defect-passivated Te-doped Cs2HfCl6 perovskite microcrystals with high efficiency and robust stability for X-ray imaging - Yanqing Zu; Run Gan; Lixia Jing; Bing Yang; Binglin Zeng; Liru Yuan; Peitao Liu; Xiaodong Li; Ailing Feng; Lei Zhou (Chemical Engineering Journal, 2026)

Reaction of oridonin with p-toluenesulfonic anhydride/p-toluenesulfonic acid: An unexpected cascade rearrangement - Zhengyang He; Ailing Tian; Feng Gao; Zongrui Hou; Xiaohuan Li (Phytochemistry Letters, 2026)

A multi-scale linear cross-modal fusion architecture for tomato leaf disease segmentation - Zaichun Yang; Lixiang Sun; Jinsheng Deng; Ailing Cai; Zhihuan Liu; Genhua Liu; Jiang Zhang; Guoxiong Zhou; Yahui Hu; Liujun Li (Computers and Electronics in Agriculture, 2026)

Effects of grazing activities on ecosystem health in three-river-source national park - Yanqin Wang; Huaju Xue; Ailing Sun; Aiqing Li; Xiaofen Wang; Jinhe Zhang (Journal of Environmental Management, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Analysis of volatile flavor compounds in bamboo shoots fermented with different water types using GC-MS and GC-IMS - Jinxuan Wang; Cuiwen Jian; Mengyu Liu; Ailing Deng; Minghao Sun; Shubo Li; Yuan Guo (International Journal of Gastronomy and Food Science, 2025)

Probiotic properties and genomic insights of Limosilactobacillus reuteri isolated from Tibetan fermented yak milk with potential anti-hyperuricemic activity - Xingjie Wang; Qiming Li; Wenyi Lai; Ailing Xie; Mengmei Zhang; Kaidi Hu; Jianlong Li; Qin Li; Ning Zhao; Xiaolin Ao; Shuliang Liu (International Dairy Journal, 2025)

SlNAP2 promotes tomato fruit ripening by directly binding the SlACS2 promoter and interacting with SlEIL3 - Xuetong Wu; Hua Fang; Dengjing Huang; Xuemei Hou; Yali Qiao; Changxia Li; Ailing Li; Yi Huang; Zhiya Liu; Yayu Liu; Weibiao Liao (Postharvest Biology and Technology, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

In Situ Biofilm Aquaculture Systems (In Situ BFSs ) for Litopenaeus vannamei : A Review - Wei Zhu; Guangnian Yuan; Zhiwen Song; Qiufen Li; Chao Liu; Ailing Xu; Yazhi Luan; Yongxin Liu (Reviews in Aquaculture, 2025)
The scale of intensive Litopenaeus vannamei aquaculture has increased over the past few decades. However, the inorganic nitrogen and suspended solids (SSs) generated during the aquaculture process are toxic to shrimp and have negative environmental effects. Therefore, removing these pollutants from aquaculture systems is a critical issue that must be addressed. In addition to the widely used recirculating aquaculture systems (RASs) and biofloc technology (BFTs), the addition of submerged substrates to L. vannamei aquaculture tanks to construct in situ biofilm aquaculture systems (in situ BFSs) is an alternative that results in favorable water quality and enables low or zero water exchange, significantly improving shrimp performance and decreasing the feed conversion ratio (FCR). This review highlights the principles, construction methods, water treatment effectiveness, and impact of in situ BFSs on L. vannamei growth as well as pathogen control. The selection of appropriate substrates and methods for nitrifying biofilm cultivation and substrate fixation can significantly affect water treatment efficiency, reduce the concentrations of harmful substances (SSs, ammonia and nitrite) and provide additional nutrients and habitats for L. vannamei , thereby increasing their survival rate and enhancing their growth performance. In addition, the integration of in situ BFSs with BFTs and algal‐symbiotic systems is discussed. In this paper, the potential for further increasing the treatment capacity of in situ BFSs through sulfur autotrophic denitrification (SAD) and electric field‐assisted biofilm systems is proposed. The application of these innovative technologies is expected to provide new insights and solutions for achieving sustainable development in L. vannamei aquaculture.

Coupled chemo-mechanical modeling of early-age pastefill material under cyclic loading - Ailing Li; Mamadou Fall; Gongda Lu (Computers and Geotechnics, 2025)

Intrinsic flame-retardant flexible polyurethane foam based on phosphorus-containing polyol with Si-O-C segment: Simultaneously improving fire safety and mechanical property - Yongjiang Li; Ailing Zhang; Yanhui Wang; Donglei Fan; Yichao Lin; Jie Liu; Tao Tang (Chemical Engineering Journal, 2025)

Identification of cell-surface receptors associated with 6-PPD quinone-induced reproductive toxicity in Caenorhabditis elegans after long-term and low-dose exposure: A primordial response including sword effect and shield effect - Shuhan Lei; Huanliang Liu; Bing Zhang; Ailing Chen; Xiaona Li; Yu Wu; Zhenyu Wang (Journal of Hazardous Materials, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

SlDCD and SlLCD increased the salt tolerance in tomato seedlings by enhancing antioxidant and photosynthesis capacity - Xinfang Chen; Dengjing Huang; Xiaoling Man; Ailing Li; Hua Fang; Siting Lu; Di Yang; Weibiao Liao (Plant Cell Reports, 2025)

How obesity and overweight affect the carbon footprint of China's healthcare: A dire situation calling for urgent action - Zhimin Shi; Lixiao Zhang; Pengpeng Zhang; Yan Hao; Xin Xiong; Xinqing Li; Ailing Liu (Environmental Impact Assessment Review, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Preparation of cellulose-based nanoparticles via electrostatic self-assembly for the pH-responsive delivery of astaxanthin - Miaoyu Gan; Ailing Cao; Luyun Cai; Xia Xiang; Jian Li; Qian Luan (Food Chemistry, 2025)

Amino oxidized sodium alginate-based humidity-resistant triboelectric nanogenerator for human motion and respiration monitoring - Xixi Wang; Na Li; Ailing Yang; Nianfeng Zhang; Wu Qiu; Dapeng Yang (Chemical Engineering Journal, 2025)

The role of BTG2/PI3K/AKT pathway-mediated microglial activation in T-2 toxin-induced neurotoxicity - Xiukuan Li; Jinyun Long; Chunyan Yao; Xiaoling Liu; Na Li; Yumeng Zhou; Dawei Li; Guiyuan Xiong; Kexue Wang; Yuhui Hao; Ka Chen; Ziyuan Zhou; et al. (Toxicology Letters, 2024)

Characteristics of inhibition of Aspergillus flavus growth and degradation of aflatoxin B1 by cell-free fermentation supernatant of Bacillus velezensis 906 - Keying Li; Si Cheng; Zhe Liu; Qingyan Pan; Xifeng Zuo; Ailing Guo; Jun Lv (Food Bioscience, 2024)

Preparation and characterization of probiotic Bacillus velezensis 906 metabolites /potassium sorbate/ polyvinyl alcohol antimicrobial blend film - Si Cheng; Chao Yin; Keying Li; Zhe Liu; Qingyan Pan; Xifeng Zuo; Ailing Guo; Huawei Ma (Food Bioscience, 2024)

Pasteurized Akkermansia muciniphila mitigates 5-FU-induced intestinal mucositis in tumor-bearing mice through suppression of the cGAS-STING pathway and epithelial cell apoptosis - Yue Teng; Jiahui Li; Chunhong Yan; Ailing Wang; Xiaomeng Ren; Xiaodong Xia (Food Bioscience, 2024)

Efficient continuous synthesis of long-chain alkylbenzenes catalyzed by ionic liquids in microreaction systems - Haoran Ma; Wei Zhao; Ping Li; Ailing Huang (Chemical Engineering Journal, 2024)

Presence of humic acid in the environment holds promise as a potential mitigating factor for the joint toxicity of polystyrene nanoplastics and herbicide atrazine to Chlorella vulgaris: 96-H acute toxicity - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; Xingyi Wei; Jingli Li; Ailing Fu; De-Sheng Pei (Chemosphere, 2024)

High ambient temperature may increase the risk of anemia in pregnancy: Identifying susceptible exposure windows - Hua Xiao; Yunlong Li; Xiaoling Liu; Qin Wen; Chunyan Yao; Yao Zhang; Weijia Xie; Wenhui Wu; Long Wu; Xiangyu Ma; Yafei Li; Ailing Ji; et al. (Science of The Total Environment, 2024)

Microbial community structure in a constructed wetland based on a recirculating aquaculture system: Exploring spatio-temporal variations and assembly mechanisms - Wenjie Tian; Qiufen Li; Zijun Luo; Chao Wu; Bo Sun; Danting Zhao; Saisai Chi; Zhengguo Cui; Ailing Xu; Zhiwen Song (Marine Environmental Research, 2024)

Triassic oceanic–continental transition of the Ganzi–Litang Ocean basin: Evidence from high-Mg andesites and Nb-enriched basalts in the Litang area, Eastern Tibet - Songtao Yan; Ailing Ding; Xuejian Dai; Tao Liu; Hu Li; Hongrui Dai; Peng Chen; Qingsong Wu; Lidong Zhu (Journal of Asian Earth Sciences, 2024)

Granular bacterial inoculant alters the rhizosphere microbiome and soil aggregate fractionation to affect phosphorus fractions and maize growth - Xiaofan Xie; Yang Liu; Gaofeng Chen; Andéole Niyongabo Turatsinze; Liang Yue; Ailing Ye; Qin Zhou; Yun Wang; Meilan Zhang; Yubao Zhang; Zhongping Li; Lam-Son Phan Tran; et al. (Science of The Total Environment, 2024)

Fabrication of bimetallic Co/Ni composite oxides on Ni-foam as a highly active monolithic membrane catalyst for the reduction of 4-nitrophenol - Xiaogang Liao; Xiaoya Wang; Li Zheng; Yifei Hu; Ailing Wu; Gang Li (Process Safety and Environmental Protection, 2024)

A label-free fluorescence and naked-eye detection for ochratoxin A based on aptamer antiparallel G-quadruplex/crystal violet - Ailing Lei; Mingda Li; Siqi Zhuo; Qianjin Li; Jianlin Li (Food Bioscience, 2024)

Sustainable utilization of feather waste to produce alkaline serine protease by genetically engineered Bacillus amyloliquefaciens - Ziyue Zhao; Zhou Li; Ailing Guo; Xuetuan Wei (Journal of Cleaner Production, 2024)

CRISPR/Cas9 gene editing in peanut by Agrobacterium tumefaciens-mediated pollen tube transformation - Ailing Li; Min Zhou; Guoting Liao; Xinyue Li; Aiqin Wang; Dong Xiao; Longfei He; Jie Zhan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Identification and functional characterization of REGULATORY PARTICLE NON-ATPASE 1a-like (AhRPN1a-like) in peanuts during aluminum-induced programmed cell death - Guoting Liao; Shuzhen Luo; Xinyue Li; Ailing Li; Yunchuan Mo; Aiqin Wang; Dong Xiao; Long-Fei He; Jie Zhan (Journal of Plant Physiology, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Discovery of acylated isoquercitrin derivatives as potent anti-neuroinflammatory agents in vitro and in vivo - Jie Liu; Ailing Hui; Jinghe Wang; Qingfeng Hu; Shengnan Li; Yuanli Chen; Zeyu Wu; Wencheng Zhang (Chemico-Biological Interactions, 2023)

A colorimetric and fluorometric dual-mode probe for Cu2+detection based on functionalized silver nanoparticles - Guixiang Yao; Shuju Fang; Pengyuan Yin; Ailing Li; Wenrong Yang; Hongbin Wang; Wei Tan (Environmental Science and Pollution Research, 2023)

Unexpected association between ambient ozone and adult insomnia outpatient visits: A large-scale hospital-based study - Dawei Li; Lili Yang; Nan Wang; Yuegu Hu; Yumeng Zhou; Ning Du; Na Li; Xiaoling Liu; Chunyan Yao; Na Wu; Ying Xiang; Yafei Li; et al. (Chemosphere, 2023)

Low-cost material combination based on PTQ10 and completely non-fused nonfullerene acceptor for high VOC organic photovoltaics - Linjiao Qin; Xianda Li; Chuanqi Dong; Jialing Zhou; Qiang Guo; Ailing Tang; Yufei Zhong; Erjun Zhou (Chemical Engineering Journal, 2023)

Mphy gene reveals the involvement of light source in the regulation of pigment metabolism in Monascus ruber - Weidong Li; Ailing Li; Wanjun Yu; Mianhua Chen; Guozhong Zhao; Yurong Wang (Food Bioscience, 2023)

The role of extreme high humidex in depression in chongqing, China: A time series-analysis - Yumeng Zhou; Ailing Ji; Enjie Tang; Jianghong Liu; Chunyan Yao; Xiaoling Liu; Chen Xu; Hua Xiao; Yuegu Hu; Yuexu Jiang; Dawei Li; Ning Du; et al. (Environmental Research, 2023)

Association between maternal short-term exposure to ambient air pollution and the risk of fetal distress: A matched case-control study - Hua Xiao; Chunyan Yao; Zongli Qi; Jianghong Liu; Xiaoling Liu; Yumeng Zhou; Enjie Tang; Yuegu Hu; Yuexu Jiang; Dawei Li; Ning Du; Na Li; et al. (Science of The Total Environment, 2023)

Pyrolysis of wood waste to enhance hydrogen production on iron-based aluminum dross - Panpan Lang; Ailing Lu; Peng Liu; Yanling Li; Xueqin Li; Tanglei Sun; Yantao Yang; Tingzhou Lei (Fuel, 2023)

Lipopolysaccharide induces inflammatory microglial activation through CD147-mediated matrix metalloproteinase expression - Chunyan Yao; Xiaoling Liu; Yan Tang; Chunmei Wang; Chenggang Duan; Xiaoyan Liu; Mingliang Chen; Yumeng Zhou; Enjie Tang; Ying Xiang; Yafei Li; Ailing Ji; et al. (Environmental Science and Pollution Research, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

TNIK influence the effects of antipsychotics on Wnt/β-catenin signaling pathway - Ruixue Yuan; Yaojing Li; Yingmei Fu; Ailing Ning; Dongxiang Wang; Ran Zhang; Shunying Yu; Qingqing Xu (Psychopharmacology, 2021)

Regional brain network and behavioral alterations in EGR3 gene transfected rat model of schizophrenia - Wenwen Gao; Guangfei Li; Xiaowei Han; Zeyu Song; Shuai Zhao; Feiyi Sun; Hong Ma; Ailing Cui; Yige Wang; Xiuxiu Liu; Yue Chen; Lu Zhang; et al. (Brain Imaging and Behavior, 2021)

Advances in physiological functions and mechanisms of (−)-epicatechin - Zhihao Qu; Ailing Liu; Penghui Li; Changwei Liu; Wenjun Xiao; Jianan Huang; Zhonghua Liu; Sheng Zhang (Critical Reviews in Food Science and Nutrition, 2021)

Study on the Release Potential of BPA and Steroid Estrogens in the Sediments of Erhai Lake, a Typical Plateau Lake of China - Jian Shen; Xueying Li; Xinze Wang; Jimeng Feng; Xiaojuan He; Shiyi Jiang; Ailing Zhou; Xiaoyan Ouyang (Bulletin of Environmental Contamination and Toxicology, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Catechins enhance skeletal muscle performance - Penghui Li; Ailing Liu; Wei Xiong; Haiyan Lin; Wenjun Xiao; Jianan Huang; Sheng Zhang; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2020)

Characterization and genome analysis of novel Klebsiella phage Henu1 with lytic activity against clinical strains of Klebsiella pneumoniae - Tieshan Teng; Qiming Li; Zhengguo Liu; Xianghui Li; Zizheng Liu; Hanshu Liu; Fangyan Liu; Longxiang Xie; Huijuan Wang; Lei Zhang; Dongdong Wu; Mingliang Chen; et al. (Archives of Virology, 2019)

Development of β-elemene and Cisplatin Co-Loaded Liposomes for Effective Lung Cancer Therapy and Evaluation in Patient-Derived Tumor Xenografts - Mingxiang Cao; Mengmeng Long; Qiuping Chen; Yapeng Lu; Qianqian Luo; Yue Zhao; Ailing Lu; Cunwang Ge; Li Zhu; Zhongping Chen (Pharmaceutical Research, 2019)

Peptide P11 suppresses the growth of human thyroid carcinoma by inhibiting the PI3K/AKT/mTOR signaling pathway - Dongdong Wu; Wenke Tian; Jianmei Li; Qianqian Zhang; Honggang Wang; Lei Zhang; Zhongwen Xie; Ailing Ji; Yanzhang Li (Molecular Biology Reports, 2019)

An Overview of Scoring Functions Used for Protein–Ligand Interactions in Molecular Docking - Jin Li; Ailing Fu; Le Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

MiR-126-3p promotes the cell proliferation and inhibits the cell apoptosis by targeting TSC1 in the porcine granulosa cells - Xiaolong Yuan; Xi Deng; Xiaofeng Zhou; Ailing Zhang; Yan Xing; Zhe Zhang; Hao Zhang; Jiaqi Li (In Vitro Cellular & Developmental Biology - Animal, 2018)

Enhancement of brain-targeting delivery of danshensu in rat through conjugation with pyrazine moiety to form danshensu-pyrazine ester - Ailing Hui; Huayang Yin; Zheng Zhang; An Zhou; Jingchao Chen; Li Yang; Zeyu Wu; Wencheng Zhang (Drug Delivery and Translational Research, 2018)

Celastrol specifically inhibits the activation of NLRP3 inflammasome - Xuesong Sang; Yihui Chen; Wei Chen; Jing Xie; Guangxun Meng; Jin Zhong; Taisheng Li; Ailing Lu (Science China Life Sciences, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Co-production of lipids, eicosapentaenoic acid, fucoxanthin, and chrysolaminarin by Phaeodactylum tricornutum cultured in a flat-plate photobioreactor under varying nitrogen conditions - Baoyan Gao; Ailing Chen; Wenyuan Zhang; Aifen Li; Chengwu Zhang (Journal of Ocean University of China, 2017)

Genetic diversity and evolutionary characteristics of type 2 porcine reproductive and respiratory syndrome virus in southeastern China from 2009 to 2014 - Jiankui Liu; Xia Zhou; Junqiong Zhai; Bing Li; Chunhua Wei; Ailing Dai; Xiaoyan Yang; Manlin Luo (Archives of Virology, 2017)

Application of an integrated biomarker response index to assess ground water contamination in the vicinity of a rare earth mine tailings site - Wantong Si; Xiaoying He; Ailing Li; Li Liu; Jisheng Li; Donghui Gong; Juan Liu; Jumei Liu; Weishou Shen; Xuefeng Zhang (Environmental Science and Pollution Research, 2016)

Engineering low phorbol ester Jatropha curcas seed by intercepting casbene biosynthesis - Chunhong Li; Ailing Ng; Lifen Xie; Huizhu Mao; Chengxiang Qiu; Ramachandran Srinivasan; Zhongchao Yin; Yan Hong (Plant Cell Reports, 2016)

Microarray data uncover the genome-wide gene expression patterns in response to heat stress in rice post-meiosis panicle - Xianwen Zhang; Hairong Xiong; Ailing Liu; Xiaoyun Zhou; Yan Peng; Zhuoxue Li; Guangyu Luo; Xiangrong Tian; Xinbo Chen (Journal of Plant Biology, 2014)

Hydrological Simulation by SWAT Model with Fixed and Varied Parameterization Approaches Under Land Use Change - Jinkang Du; Hanyi Rui; Tianhui Zuo; Qian Li; Dapeng Zheng; Ailing Chen; Youpeng Xu; C.-Y. Xu (Water Resources Management, 2013)

Biodegradation of ethanethiol in aqueous medium by a new Lysinibacillus sphaericus strain RG-1 isolated from activated sludge - Shungang Wan; Guiying Li; Taicheng An; Bin Guo; Lei Sun; Lei Zu; Ailing Ren (Biodegradation, 2010)

Effects of litter quality and climate change along an elevation gradient on litter mass loss in an alpine meadow ecosystem on the Tibetan plateau - Guangping Xu; Yigang Hu; Shiping Wang; Zhenhua Zhang; Xiaofeng Chang; Jichuang Duan; Caiyun Luo; Zengguo Chao; Ailing Su; Qiaoyan Lin; Yingnian Li; Mingyuan Du (Plant Ecology, 2010)

Temperature sensitivity of nutrient release from dung along elevation gradient on the Qinghai–Tibetan plateau - Guangping Xu; Zengguo Chao; Shiping Wang; Yigang Hu; Zhenghua Zhang; Jichuang Duan; Xiaofeng Chang; Ailing Su; Caiyun Luo; Yingnian Li; Mingyuan Du (Nutrient Cycling in Agroecosystems, 2010)

Effect of warming and grazing on litter mass loss and temperature sensitivity of litter and dung mass loss on the Tibetan plateau - CAIYUN LUO; GUANGPING XU; ZENGGUO CHAO; SHIPING WANG; XINGWU LIN; YIGANG HU; ZHENHUA ZHANG; JICHUANG DUAN; XIAOFENG CHANG; AILING SU; YINGNIAN LI; XINQUAN ZHAO; et al. (Global Change Biology, 2010)
Knowledge about the role of litter and dung decomposition in nutrient cycling and response to climate change and grazing in alpine ecosystems is still rudimentary. We conducted two separate studies to assess the relative role of warming and grazing on litter mass loss and on the temperature sensitivity of litter and dung mass loss. Experiments were conducted for 1–2 years under a controlled warming–grazing system and along an elevation gradient from 3200 to 3800 m. A free‐air temperature enhancement system (FATE) using infrared heaters and grazing significantly increased soil temperatures (average 0.5–1.6 °C) from 0 to 40 cm depth, but neither warming nor grazing affected soil moisture except early in the growing seasons at 30 cm soil depth. Heaters caused greater soil warming at night‐time compared with daytime, but grazing resulted in greater soil warming during daytime compared with night‐time. Annual average values of the soil temperature at 5 cm were 3.2, 2.4 and 0.3 °C at 3200, 3600 and 3800 m, respectively. Neither warming nor grazing caused changes of litter quality for the first year of the controlled warming–grazing experiment. The effects of warming and grazing on litter mass losses were additive, increasing litter mass losses by about 19.3% and 8.3%, respectively, for the 2‐year decomposition periods. The temperature sensitivity of litter mass losses was approximately 11% °C −1 based on the controlled warming–grazing experiment. The annual cumulative litter mass loss was approximately 2.5 times that of dung along the elevation gradient. However, the temperature sensitivity (about 18% °C −1 ) of the dung mass loss was about three times that of the litter mass loss. These results suggest greater warming at night‐time compared with daytime may accelerate litter mass loss, and grazing will enhance carbon loss to atmosphere in the region through a decrease of litter biomass and an increase of dung production with an increase of stocking rate in future warmer conditions.

The novel 5bp deletion polymorphism in the promoter region of bovine ACRP30 gene - Liangzhi Zhang; Hong Chen; Xianyong Lan; Cunfang Zhang; Li Zhang; Ailing Zhang; Qin Zhang; Cunlei Lei; Hanyang Zhang (Molecular Biology Reports, 2009)

Molecular phylogeny of the domesticated silkworm,Bombyx mori, based on the sequences of mitochondrialcytochrome b genes - Ailing Li; Qiaoling Zhao; Shunming Tang; Zhifang Zhang; Shenyuan Pan; Guifang Shen (Journal of Genetics, 2005)

The present situation, types and changes of China’s environment - Wangbing Ren; Wei Wu; Ailing Li (Chinese Geographical Science, 1999)